The Emergence of a Phoneme-Sized Unit in L2 Speech Production: Evidence from Japanese–English Bilinguals - Nakayama, Mariko; Kinoshita, Sachiko; Verdonschot, Rinus G. (Frontiers in Psychology, 2016)
Recent research has revealed that the way phonology is constructed during word production differs across languages. Dutch and English native speakers are suggested to incrementally insert phonemes into a metrical frame, whereas Mandarin Chinese speakers use syllables and Japanese speakers use a unit called the mora (typically a CV cluster such as “ka” or “ki”). The present study is concerned with the question how bilinguals construct phonology in their L2 when the phonological unit size differs from the unit in their L1. Japanese-English bilinguals of varying proficiency read aloud English words preceded by masked primes that overlapped in just the onset (e.g., bark-BENCH) or the onset plus vowel corresponding to the mora-sized unit (e.g., bell-BENCH). Low-proficient Japanese-English bilinguals showed CV priming but did not show onset priming, indicating that they use their L1 phonological unit when reading L2 English words. In contrast, high-proficient Japanese-English bilinguals showed significant onset priming. The size of the onset priming effect was correlated with the length of time spent in English-speaking countries, which suggests that extensive exposure to L2 phonology may play a key role in the emergence of a language-specific phonological unit in L2 word production.